Improved Machining Performance Through Turn-Milling - Kaveh Rahimzadeh Berenji; Erhan Budak (Journal of Machine Engineering)
As a multi-axis metal cutting operation, turn-milling has the combined characteristics of conventional turning and milling operations involving rotating workpiece and milling tool with linear feed motion in the workpiece axis direction. Although turn-milling offers many advantages in machining of complex and hard-to-cut materials due to its flexible kinematics, the process presents specific challenges. The main objective of this paper is to present an overview of turn-milling operations from different perspectives. In this regard, first the advantages of turn-milling in terms of tool life are presented. An analytical approach is given based on process kinematics to achieve better surface quality and productivity simultaneously. Additionally, the uncut chip geometry and the cutting force models are presented with experimental verification.